ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN DEVISA DI INDONESIA - Norita Fitria; Aris Soelistyo; Dwi Susilowati (Jurnal Ilmu Ekonomi, 2021)
The purpose of this study is to analyze what factors affect foreign exchange reserves in Indonesia. The focus in this study is the variables that affect changes in foreign exchange reserves in the 1999-2019 period are non-oil and gas exports, the rupiah exchange rate, foreign debt and inflation as independent variables. Using an open economy model and Keynes's balance of payments, the analytical tools used in this study are the PAM regression model (Partial Adjustment Model) and the adaptive expectation model to see the long-term and short-term effects of the independent variable on the dependent variable. The results of this study show that simultaneously non-oil and gas exports, the rupiah exchange rate, foreign debt and inflation affect Indonesia's foreign exchange reserves, while partially non-oil exports and the rupiah exchange rate significantly and positively affect Indonesia's long-term and short-term foreign exchange reserves, while debt foreign exchange and inflation are not  significant and negatively affect long-term and short-term foreign exchange reserves. Non-oil exports, rupiah exchange rate, foreign debt and inflation can explain Indonesia's foreign exchange reserves of 97%, of which the remaining 3% is explained by other variables not included in this study.